SUICIDAL TENDENCY AND STRESS AMONG COLLEGE STUDENTS (International Journal of Food and Nutritional Sciences, 2022)
Suicide is the second most common cause of death in young adults worldwide. Suicide is often committed out of despair, or attributed to some underlying mental disorder which includes depression, bipolar disorder, schizophrenia, alcoholism and drug abuse. Financial difficulties, troubles with interpersonal relationships and other desirable situation play a significant role but they are prone to commit suicide, this is very serious issue. Generally it assumes that students who dont have to face above cited problems except stress. Therefore, the present study aimed to find out the suicidal tendency and stress among college students. For this purpose a total of 100 college students were selected from varies college in ahmedabad city i.e. Arts college (N=50) and commerce college (N=50). The sample included both boys and girls students in equal number. Two scales namely suicidal tendency scale and Stress Scale were administered to all the subjects. Obtained scores were analyzed with help ‘t test. Results revealed that significant difference in suicidal tendency and stress observed with respect Arts and Commerce College students. It also found that significant difference in suicidal tendency and stress between boys and girls students of Commerce College. While the significance positive correlation between Suicidal tendency and Stress reveals 0.24